CLINICAL AND RADIOLOGICAL APPROACH OF POSTERIOR REVERSIBLE ENCEPHALOPATHY SYNDROME ON ECLAMPSIA - Fakhrurrazy, Fakhrurrazy; Surdhawati, Herly Maulida (Malang Neurology Journal, 2017)
Posterior reversible encephalopathy syndrome (PRES) is rare clinico-neuroradiologic condition and not commonly reported in the literature, a recently recognized syndrome characterized clinically by headache, confusion, seizure and visual loss associated, with imaging findings of bilateral cortical and subcortical oedema, predominantly posterior cerebral lesions (mainly occipito-parietal). Posterior reversible encephalopathy syndrome is an uncommon complication of severe preeclampsia/ eclampsia. The objective of this study is to report PRES case on eclampsia with clinical and radiological approach. We report a case of woman, 34 years old woman, with chief complaint tonic clonic general seizure and sudden headache previously. This patient had pregnancy 8 gestational month and had pregnancy termination with cesarean section recently. Patient had loss of consciousness, vision disturbance, and weakness of right extremities, all this symptom become well during treatment. The result of laboratory examination was HELLP syndrome (haemolysis, elevated liver enzymes and low-platelets). Head CT scan showed hypodense lesion in left parietooccipital region and MRI on T2W and T2FLAIR ADC MAPS found hyperintens lesion in right and left parietooccipital. Then it can be concluded that it have been reported cases of eclampsia with PRES with symptom of headache, seizure, mental status disturbance, visual disturbances. The pathological association between PRES and HELLP syndrome in a patient with eclampsia is poorly described.